MIDWIFE CARE FOR NORMAL NEWBORN BABIES NY. N AT HJ. HENDRAYATNI CLINIC, PEMATANGSIANTAR CITY - Lusi Utami, Ria (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Post episiotomy post pain rates vary due to incision and suturing at the time of episiotomy causing sharp pain with different levels This is due to the activation of peripheral nociceptors which is a special receptor conducting noxious stimulus. There are as many as 70.9% of mothers experiencing pain around the episiotomy sutures and there are as many as 73% post episiotomy pain is very disturbing maternal comfort resulting in difficulty during bowel movements, urination, and insomnia. Scientifie Writing is at implementing Nutrition Midwifery Management at Ny “S” with Episiotomy Injury at Universitas Efarina Pematngsiantar Year 2020 in accordance with 7 steps Varney and SOAP. The result of a case study that had been done on Ny “S” with episiotomy injury, no obstacles found during the care provided. The results of a case study that had been done on Mrs “S” with episiotomy injury, no obstacles found during the care provided. Monitoring is done 5 times for approximately 1 month. During the treatment and home visits, there was pain in the episiotomy wound since after the mother gave birth on June 02, July 2020 until the 4th day of the puerperium, 1 week postpartum Mrs “S” did not feel episiotomy wound pain, but 2 week back maternal period feel the pain in her genitals after doing coitus. After care and monitoring on Ny “S” the pain has stopped, and the episiotomy suture has dried and healed. The conclusion of the case study that is 7 steps Varney and SOAP used for the proces of problem solving obstetrics have been done assessment and data analysis on the case of Ny “S” with episiotomy injury in Klinik Mandiri Midwife M.